2019
DOI: 10.22207/jpam.13.4.28
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biofertilizer Production and its Application in Plants using Pot Culture Technique

Abstract: Mass production of Bacillus thuringiensis A5-BRSC culture as biofertilizer, using cheap carbon sources revealed that mashed potato is the most effective carbon source followed by arrowroot and liquid waste of boiled rice. Biomass was mixed with charcoal, the carrier, and applied to the pots to study its plant growth stimulating effect using Abelmoschus esculentus as test plant. Biofertilizer inoculated plants showed high shoot and root length, high numbers of leaves, more numbers of fruits, increased fruit wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Bacillus thuringiensis has been reported to exhibit several growth accelerating activities like phosphate solubilization, phytohormone production, siderophore production etc 8,12,31 . The bacterial strain used in the present study was previously reported to exhibit an appreciable amount of phosphate solubilizing and phytohormone producing activity, as well as stimulated the growth of potted plants 20,24 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bacillus thuringiensis has been reported to exhibit several growth accelerating activities like phosphate solubilization, phytohormone production, siderophore production etc 8,12,31 . The bacterial strain used in the present study was previously reported to exhibit an appreciable amount of phosphate solubilizing and phytohormone producing activity, as well as stimulated the growth of potted plants 20,24 .…”
Section: Discussionmentioning
confidence: 93%
“…The growth promoting effects of the biofertilizer used in the present study was already investigated in pot condition 20 . The aim of the present study is to explore such beneficial effects of same biofertilizer in field condition, using Abelmoschus esculentus as test plants in comparison to the plants not treated with biofertilizer.…”
Section: Introductionmentioning
confidence: 99%